Graduate Student Perceptions of the Effectiveness of Individual Development Plans - Arnaud, Emmanuelle; Cahill, Sarah (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2024)
Individual development plans (IDPs) are increasingly being used in higher education to provide personalized guidance to students that can foster a more purposeful and productive education experience. In this study, we document the graduate student’s perspective on the effectiveness of the IDP based on responses from students in course- and thesis-based masters and doctoral programs in science and social science. Informational interviews and mentor meetings were seen as the most useful components of the IDP. Students also felt that the IDP had helped them with many career development activities, but they also highlighted several challenges. Findings from a content and thematic analysis provide insight for those interested in implementing the IDP at their own institution.